Protection and development strategies for traditional ethnic minority villages in Sichuan: A case study of a Qiang traditional village - Hua, Z. Z.; Omar, Jamaludin; Doh, Shu Ing (Penerbit UTEM, 2024)
The traditional ethnic minority villages in Sichuan Province are renowned for their profound historical heritage and unique cultural value. However, with the advancement of modernization, these villages are facing numerous challenges such as population loss, dilution of traditional culture, and environmental degradation. This study investigates the preservation and development strategies for traditional ethnic minority villages in Sichuan, focusing on the Qiang ethnic village of Xiuxi. Through field surveys, interviews, and literature research, the study provides a comprehensive understanding of Xiuxi Village's cultural, social, and environmental context. Several strategies are proposed to address these challenges, including strengthening community participation, enhancing tourism development and management, and modernizing agriculture. By implementing these measures, the study aims to protect cultural heritage while promoting economic development, ensuring the sustainable development of Xiuxi Village, and improving the residents' quality of life.